Review of The Security Check Process at The Passenger Security Checkpoint (PSCP) to Improve Flight Security at Soekarno-Hatta International Airport - kardi, Kardi; Amir, Elvi; Adriansyah, Fery; Kumala Pratiwi, Ayu (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
Threats to aviation security have increased, firearms technology has developedrapidly, including the existence of firearms using a magazine in which there are 4 (four) rounds of ammunition and firearms with revolver type with titanium material which is light, strong and can store 5 (five) rounds of ammunition so that it can shoot with a certain amount of ammunition contained in it. In addition to thedevelopment of firearms, there are also sharp weapons that are not made of metal (non-metallic knife) where the developmentof this sharp weapon is in stark contrast to the technology of security equipment used at terminal 3 Soekarno-Hatta International Airport, the majority of which still use metal detectors. With the development of weapons technology, both firearms and sharp weapons, it is this equipment, procedures and capabilities of aviation security personnel, especially at Terminal 3 of Soekarno- Hatta Airport, that can be improved to anticipate technologicaldevelopments in aviation crimes, so that aviation security and safety is the goal. in aviationin Indonesia can be realized. The Ministry of Transportation seeks to assist every airport operator in determining standards for each personel, equipment and procedures to anticipate increasing aviation security threats through the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 28 of 2021 concerning the National Aviation Security Education and Training Program.